Expanding the evidence for managing metformin poisoning to support decision-making. (3rd April 2023) - Roberts, Darren M.; Ghannoum, Marc
Abstract: Introduction: Metformin-associated lactic acidosis is a well-described and commonly encountered condition associated with significant morbidity and mortality. Patients with metformin-associated lactic acidosis are frequently managed in the intensive care unit with supportive care, including volume resuscitation and consideration of an extracorporeal treatment to correct metabolic acidemia and remove metformin and lactate. Extracorporeal Treatments in Poisoning Workgroup: The Extracorporeal Treatments in Poisoning Workgroup published evidence-based consensus recommendations in 2015 regarding the use of extracorporeal treatment in metformin toxicity. These recommendations list both clinical and biochemical indications, and they outline the rationale and evidence supporting each recommendation. New research since recommendations were published: Subsequent publications have provided new information regarding metformin-associated lactic acidosis and its treatment. A retrospective study showed that patients who did not meet the Extracorporeal Treatments in Poisoning Workgroup criteria for initiation of an extracorporeal treatment had a 100% survival. In patients who met the criteria, survival was approximately 75%; only 66% of these patients received an extracorporeal treatment, and this treatment did not appear to impact survival. Two other retrospective studies in patients diagnosed with metformin-associated lactic acidosis noted that extracorporeal treatments did not improve survival. However, those who received an extracorporeal treatment were more severely ill, potentially supporting a benefit from this intervention. A systematic review of patients receiving continuous kidney replacement therapy identified an overall survival that was higher than the overall survival in patients included in the Workgroup publication. This led the authors to suggest that intermittent hemodialysis may not be the preferred treatment for metformin toxicity. However, a closer look at the Workgroup data identified improved survival with each decade since the initial reports in the 1970s. Furthermore, there are multiple reports of persistent metformin-associated lactic acidosis that did not improve with standard continuous kidney replacement therapy, prompting an increase in the dosage of the extracorporeal treatment. The data supporting these observations are largely derived from retrospective studies, which have inherent biases, so prospective studies are required. Prescribing extracorporeal treatments for patients with metformin poisoning: Case-based decision-making is always necessary, but in general, we continue to follow the Extracorporeal Treatments in Poisoning Workgroup criteria because a convincing reason for changing these has not yet been presented. This includes the use of intermittent hemodialysis where possible, particularly in cases of severe poisoning. For patients with less severe poisoning or when intermittent hemodialysis is not readily available, it is reasonable to trial continuous modalities with careful observation for deterioration.